A Method for Identifying Germplasm that Exhibit Multiple Mutations in the Fatty Acid Synthetic Pathway of Perilla frutescens. (4th September 2020) - Zhang, Xueting; Feng, Shuhan; Yang, Wei; Shen, Qi; Chen, Sha
Abstract: A method using gas chromatography–mass spectroscopy (GC–MS) was developed to assess phenotypic differences in the fatty acid composition of 143 accessions of Perilla frutescens varieties that originated from different Chinese provinces, Japan, and Britain. Thirty‐six compounds identified in the analysis included a number of saturated fatty acids and positional isomers of unsaturated fatty acids. A wide range in phenotypic variation was noted within each of five major fatty acids [16:0, 6.8–11.5%; 18:0, 1.7–11.9%; 18:1 (n‐9), 12.3–28.0%; 18:2 (n‐9, 12), 9.6–21.6%; 18:3 (n‐9, 12, 15), 41.4–56.6%]. Many accessions exhibited potential gene mutations or differences in gene copy number for multiple steps of fatty acid synthesis. For example, PCA models were developed to distinguish groups of accessions that exhibited low‐16:0, low‐18:1, high‐18:3 traits, and others that exhibited high‐16:0, high‐18:1, low‐18:3 traits. We believe this approach should improve the process for the identification of genetic resources that help reveal the complex nature of biological regulation not only of fatty acid metabolism but other metabolic processes as well.